Consumer-Driven Demand and Operations Management Models A Systematic Study of Information-Technology-Enabled Sales Mechanisms - Tang, Christopher S.; Netessine, Serguei; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
The consumer demand functions that drive traditional retail sales are the well-defined functions of price and product attributes (e.g., quality, style trends, etc.). However, these new sophisticated selling techniques-examples are mixed sales channels, portals, group buying, and auctions, each of which is enabled by information technologies, the Internet, or both-are changing and expanding consumer-driven demand in many ways. The underlying pattern of demand created by these evolving mechanisms will be a marked departure from traditional factors driving consumer demand. To analyze and understand rational and strategic consumer demand, the editors have divided the book into five discrete sections that first consider rational consumer behavior and the endogenous decision making mechanisms behind it. They then present sections on organizational strategies, product strategies, operational strategies, and, finally, pricing strategies for managing rational/strategic consumer behavior. Together, this handbook provides the state-of-the-art OM models that will help the reader to understand and effectively respond to increasingly rational purchasing behavior. CONSUMER-DRIVEN DEMAND AND OPERATIONS MANAGEMENT MODELS has been developed by two of the leading researchers in the POM/Marketing interface. It is comprised of commissioned chapters by top research scholars in supply chain management, revenue management, and e-commerce among others, all of which are grounded in information technologies and consumer demand research.
Rational Consumer Behavior: Endogenous Decision Making Mechanisms -- Cheap Talk in Operations: Role of Intentional Vagueness -- Product Design in a Market with Satisficing Customers -- The Effect of Assortment Rotation on Consumer Choice and Its Impact on Competition -- Models of Herding Behavior in Operations Management -- Organizational Strategies for Managing Rational/Strategic Consumer Behavior -- Internet-Based Distribution Channel for Product Diversion with Potential Manufacturer's Intervention -- Managing Client Portfolio in a Two-Tier Supply Chain -- Strategic Customer Behavior and the Benefit of Decentralization -- Product Strategies for Managing Rational/Strategic Consumer Behavior -- Is Assortment Selection a Popularity Contest? -- Product Design, Pricing, and Capacity Investment in a Congested Production System -- Selling to Strategic Customers: Opaque Selling Strategies -- Competing Through Mass Customization -- Operational Strategies for Managing Rational/Strategic Consumer Behavior -- Counteracting Strategic Consumer Behavior in Dynamic Pricing Systems -- Mitigating the Adverse Impact of Strategic Waiting in Dynamic Pricing Settings: A Study of Two Sales Mechanisms -- The Impact of Strategic Consumer Behavior on the Value of Operational Flexibility -- Capacity Rationing with Strategic Customers -- Strategic Behavior in Supply Chains: Information Acquisition -- Shaping Consumer Demand through the Use of Contingent Pricing -- Strategic Consumer Response to Dynamic Pricing of Perishable Products -- Strategic Behavior in Supply Chains: Information Acquisition.
Keywords: ECONOMICS; INFORMATION SYSTEMS; MARKETING; BUSINESS LOGISTICS; MANAGEMENT INFORMATION SYSTEMS; ECONOMICS/MANAGEMENT SCIENCE; OPERATIONS RESEARCH/DECISION THEORY; INFORMATION SYSTEMS APPLICATIONS (INCL.INTERNET).; PRODUCTION/LOGISTICS.; E-COMMERCE/E-BUSINESS.; BUSINESS INFORMATION SYSTEMS; MARKETING